Development and validation of a novel immunotype for prediction of overall survival in patients with clear cell renal cell carcinoma - Yu, Deshui; Zhang, Xuanzhi; Gao, Lixia; Qian, Subo; Tang, Hong; Shao, Ning (Frontiers in Oncology, 2022)
Background: Clear cell renal cell carcinoma (ccRCC) is a highly immunogenic tumor. The purpose of the present study was to establish a novel immunotype for different immune infiltration and overall survival (OS) of patients with ccRCC. Methods: Based on the Cancer Genome Atlas Project (TCGA) database (discovery set), a novel immunotype was established using ssGSEA methods. The databases of Fudan University Shanghai Cancer Center (FUSCC) and Xinhua Hospital Affiliated to Shanghai Jiaotong University School of Medicine (XHH) served as an external validation set. GSEA was carried out to identify the immunotype associated signal transduction pathways. Results: A total of 652 ccRCC patients were included in our study. We constructed a novel immunotype of ccRCC to classify patients into three groups: high-immunity, moderate-immunity and low-immunity. The high-immunity and moderate-immunity groups had higher ImmuneScores, ESTIMATEScores, StromalScores, and lower tumor purity than that of low-immunity group in both sets. Additionally, the patients from the high-immunity and moderate-immunity groups had longer survival than patients from low-immunity group in both discovery set and validation set. (HR=2.54, 95%CI: 1.56-4.13, p < 0.01; HR=2.75, 95%CI: 1.24-6.11, p = 0.01). Conclusion: In summary, we defined a novel immunotype of ccRCC. The immune types could be used as a clinical predictive tool to identify ccRCC patients with different survival. In addition, the inmmune-related biological signaling pathway also brought new insights on the mechanism of ccRCC.